Valorization of green biomass Azolla pinnata fern: multi-parameter evaluation of processing conditions on protein extractability and their influence on the physicochemical, structural, techno-functional properties and protein quality - Qoms, Mohammed S; Arulrajah, Brisha; Shamsudin, Rosnah; Wan Ibadullah, Wan Zunairah; Saari, Nazamid (John Wiley & Sons Ltd., 2022)
BACKGROUND: This study determined the effect of processing conditions on protein extractability from Azolla pinnata fern, and their influence on the physicochemical, structural, techno-functional properties and protein quality.